The independent effects of second hand smoke exposure and maternal body mass index on the anthropometric measurements of the newborn - Wahabi, Hayfaa A (BMC Public Health, 2013)
BACKGROUND: Exposure to tobacco smoke during pregnancy, whether as active smoking or by exposure to secondhand smoke (SHS), is associated with adverse pregnancy outcomes including low birth weight (LBW) and small for gestational age infants due to the effect of tobacco on the anthropometric measurements of the newborn. This effect might be masked by maternal obesity as it increases fetal weight. The objectives of this study were to estimate the independent effects of maternal exposure to SHS and maternal body mass index (BMI) on the anthropometric measurements and on the prevalence of macrosomia and LBW among term infants. METHODS: Data were collected from women in the postnatal ward following delivery. Participants were stratified into six groups based on the BMI (underweight <18 kg/m(2), non-obese 18–29.9 kg/m(2), and obese ≥30 kg/m(2)) and the SHS exposure status (exposed and non- exposed), to examine the independent effects of BMI and SHS on infants’ anthropometry. Multiple regression analysis was used to explore the independent associations between the six groups and the risk of delivering a macrosomic or LBW infant. RESULTS: Infants of women exposed to SHS had significantly reduced anthropometric measurements compared to infants of unexposed women. The odds of delivering a macrosomic baby increased to 9-fold for women with BMI of ≥30 kg/m(2) compared to non-obese women; odds ratio (OR) 9.18, 95% Confidence Interval (CI) (1.01, 9.37); p = 0.04, this risk was attenuated to 1.5-fold in women exposed to SHS, OR 1.53, 95% CI (1.19, 12.1); p < 0.0001. The odds of delivering an LBW infant were more than doubled in underweight women compared to non-obese women, OR 2.15, 95% CI (1.001, 4.57); p = 0.034, and were further increased to almost 3-fold for women who were exposed to SHS, OR 2.71, 95% CI (1.82,4.045); p = 0.02. CONCLUSION: Exposure to SHS was associated with reduced anthropometric measurements of the newborn and increased rate of LBW infants, irrespective of maternal BMI. Maternal obesity was associated with increased risk of delivering a macrosomic infant; conversely maternal underweight was associated with increased risk of delivering an LBW infant.